Cardiac and coronary CT comprehensive imaging approach in the assessment of coronary heart disease. Issue 15 (7th July 2011) - Williams, M C; Reid, J H; McKillop, G; Weir, N W; van Beek, E J R; Uren, N G; Newby, D E
Abstract : Cardiac CT is a rapidly advancing technology. Non-invasive CT coronary angiography is an established technique for assessing coronary heart disease with accuracy similar to invasive coronary angiography. CT myocardial perfusion imaging can now identify perfusion defects in animal models and humans. MRI is the current 'gold standard' for the assessment of myocardial viability, but it is now also possible to assess delayed enhancement by CT. This has led to the possibility of a 'one-stop shop' for cardiovascular imaging that would provide information on anatomy, function, perfusion and viability in one rapid diagnostic test at a radiation dose equivalent to contemporary nuclear medicine imaging. This review discusses the current status of 'one-stop shop' cardiac CT assessment, clinical utility and directions for future research.